2022
DOI: 10.3389/fcimb.2021.743454
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Disulfide (DADS) Ameliorates Intestinal Candida albicans Infection by Modulating the Gut microbiota and Metabolites and Providing Intestinal Protection in Mice

Abstract: Diallyl disulfide (DADS), a garlic extract also known as allicin, has been reported to have numerous biological activities, including anticancer, antifungal, and inflammation-inhibiting activities, among others. Although many studies have assessed whether DADS can treat Candida albicans infection in vitro, its in vivo function and the underlying mechanism are still not clear. Accumulated evidence has implicated the gut microbiota as an important factor in the colonization and invasion of C. albicans. Thus, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 82 publications
0
14
1
Order By: Relevance
“…Rifaximin affected Trp synthesis in the gut microbiota [ 58 ]. Diallyl disulfide (DADS) altered the gut microbial community structure and metabolic profile in mice [ 59 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…Rifaximin affected Trp synthesis in the gut microbiota [ 58 ]. Diallyl disulfide (DADS) altered the gut microbial community structure and metabolic profile in mice [ 59 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…Garlic is a recognized prebiotic; thus, allicin can be metabolized into diallyl disulfide (DAD) and diallyl trisulfide (DAT) to regulate gut microbiota composition and disrupt TMA production in ApoE −/− mice with high concentrations of carnitine ( Panyod et al, 2022 ). Following allicin treatment, the proportions of Bifidobacterium, Lactobacillus, Bacteroidales, and Clostridiales significantly increased in the gut ( Shi et al, 2019 ), while those in some pathogenic bacteria, such as Proteobacteria, Escherichia–Shigella, and Streptococcus, drastically reduced ( Hu et al, 2021 ). Moreover, allicin also regulates the metabolites of gut microbiota, such as upregulating SCFA, while downregulating secondary BAs, TMAO, and indoles, stimulating brown adipose tissue activation, browning in white adipose tissues ( Zhang et al, 2020 ), decline in lipid accumulation in the liver, and weight loss in obese mice ( Shi et al, 2019 ).…”
Section: Natural Compounds In Herbal Medicine Regulating Intestinal F...mentioning
confidence: 99%
“…In the BG group, we also observed an increased abundance of Ruminococcaceae_UCG-007 and Ruminiclostridium_5 , which have rarely been reported previously. Ruminococcaceae is generally considered a beneficial bacterium colonized in the cecum and colon and can degrade various polysaccharides and fibers to produce SCFAs ( Huang et al, 2021 ), it also presents an effect to reduce intestinal inflammation ( Hu et al, 2021 ). Moreover, findings from prior research showed that the increase of Ruminiclostridium_5 was associated with positive health states, whereas reduced levels are associated with negative health states.…”
Section: Discussionmentioning
confidence: 99%